Keseragaman dan Kondisi Karang Family Acroporidae di Kukusan Besar, Labuan Bajo, Flores, Nusa Tenggara Timur - Tobing, Johannes Lumban; Arthana, I Wayan; Kartika, I Wayan Darya (Current Trends in Aquatic Science; Vol 6 No 2 (2023), 2023)
Kukusan Besar, Labuan Bajo, which is located in East Nusa Tenggara is one of the fertile waters that was a diversity of marine biota in the form of coral reefs. The purpose of this study was to determine the uniformity and condition of corals, especially the corals of the Acroporidae Family. This research was carried out from November 2021–April 2022. Determination of coral data collection points used a purposive sampling method. Retrieval of coral data using the underwater photo transect (UPT) method, with the transect spread along 50 meters in the direction of the coastline at every point of depth of 3, 5 and 7 meters. Underwater photos were analyzed using CPCe software. Coral cover at a depth of 3 meters is 29.12%. The depth of 5 meters is 36.54% and at a depth of 7 meters is 42.18%. At depths of 3 and 5 meters the corals of the Acroporidae family are dominated. The highest diversity index is found at a depth of 7 meters with a value of 2.20. The highest uniformity index was found at a depth of 5 meters with a value of 0.69. Family Acroporidae at a depth of 3 and 5 meters found 4 genera namely Acropora, Montipora, Astreopora and Anacropora , while at a depth of 7 meters there were only 2 genera namely Acropora and Montipora.